Quality of Employment in Small and Medium Enterprises in Romania - Daniela PASNICU; Ghenadie CIOBANU (Revista de Management Comparat International)
In this article we propose to discuss the quality of employment in SMEs in Romania. We have debated the role of small and medium-sized enterprises in the Romanian economy, public policy proposals to create an ecosystem that promotes transformation of structure, resilience and development in SMEs, the presentation of the situation of the SME sector at the regional level, the evolution of the innovation typology, 2010-2012, the major difficulties faced by SMEs. In order to have an overview and to answer a series of questions about the quality of occupation in the Romanian SMEs, and their perspective, we have performed a radiography of some works from the field of international experience.